Interpretation of the traditional proverb “jer basuki mawa beya” on abnormal audit fees in the context of improving audit quality - Denari Dhahana Edtiyarsih; Erina Sudaryati; Sasongko Budisusetyo (Universitas Hayam Wuruk Perbanas, 2021)
East Java Province is a province in Indonesia that has cultural diversity and uniqueness. This is reflected, among other things, by the number of proverbs (in Javanese: unen-unen) used by the people of East Java. One of the popular Javanese proverbs, traditional sayings that express a perceived truth based on common sense or experience, in East Java Province is ‘Jer Basuki MawaBeya’ which means that all success requires sacrifice, or in other words, if someone wants to achieve success, there must be a cost. In the context of improving audit quality, if a company decides to employ external auditor services, the company must pay fees for the external auditor services. The abnormal audit fees paid by the company will have an effect on the increase in audit quality.